Tissue engineered biomimetic corneas for promoting corneal regeneration - McLaughlin, Christopher Ryan (University of Ottawa (Canada), 2009)
Corneal transplantation with allograft tissue is currently the gold standard treatment for treating corneal damage following trauma or disease. However the supply of good quality donor tissue cannot meet the demand, especially in developing countries. Currently, the only alternative treatment option has been the use of corneal prostheses (keratoprostheses) but these do not permit integration with the host tissue. We utilized a regenerative medicine approach to enhance the natural ability of the cornea to regenerate by providing an acellular but highly bioactive scaffold to serve as a corneal extracellular matrix (ECM) substitute. The corneal substitutes tested were based on the predominant ECM protein found in the cornea, which is type I collagen. Cross-linked collagen corneal scaffolds were formed into the appropriated dimensions and cross linked using a simple methodology, and tested in vitro to assure that they would support cellular growth of epithelial cells and nerves. The most promising candidate implants were then implanted into a range of animal models as either lamellar grafts, or full thickness grafts by lamellar and penetrating keratoplasties, respectively. Following implantation, it was observed that the scaffolds promoted regeneration of the corneal epithelial and stromal cells. The implants themselves were remodelled, observed through biotin conjugation, to give a seamless host-graft interface. The grafts remained stably integrated. At 12 months post implantation, the implanted corneas had comparable mechanical properties compared to contralateral controls. Nerves had reinnervated the cornea at densities comparable to controls and were shown to be functionally active, capable of responding to external stimuli through electrophysiological testing. We were also able to improve the mechanical properties of our gels by incorporating the biomimetic molecule 2-methacryloyloxyethyl phosphorylcholine (MPC), which allowed for full thickness transplantation into guinea pigs. Finally, with the advent of recombinant human collagen, we were able to create a novel class of human based materials for corneal implantation, which were successfully transplanted into pigs. Type III recombinant human collagen, a minor component of the human cornea, showed superior optical transmission compared to type I collagen gels, and both showed stable integration, with corneal regeneration of cells, tear film, and nerves. Substantially more work is needed to determine the limits of this approach in treating corneal blindness, i.e. what clinical causes of blindness can be treated in this manner. Nevertheless, we have demonstrated that a simple, ECM mimetic could promote the regeneration of corneal cell types, and the reinnervation of functional nerves, in a stable and seamless fashion.
Keywords: Biology, Molecular.